2015
DOI: 10.1128/iai.00480-15
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Multifunctional Broadly Reactive T Cell Responses by a Plasmodium vivax Circumsporozoite Protein Recombinant Chimera

Abstract: dPlasmodium vivax is the most widespread species of Plasmodium, causing up to 50% of the malaria cases occurring outside subSaharan Africa. An effective vaccine is essential for successful control and potential eradication. A well-characterized vaccine candidate is the circumsporozoite protein (CSP). Preclinical and clinical trials have shown that both antibodies and cellular immune responses have been correlated with protection induced by immunization with CSP. On the basis of our reported approach of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…1A,B ). We have previously validated the relevance of using this topology for the design of chimeric proteins to improve the immunogenicity of P. yoelii and P. vivax antigens in murine models 9 24 25 26 27 . The promiscuous T cell epitopes (i.e.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…1A,B ). We have previously validated the relevance of using this topology for the design of chimeric proteins to improve the immunogenicity of P. yoelii and P. vivax antigens in murine models 9 24 25 26 27 . The promiscuous T cell epitopes (i.e.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, PvRMC-MSP1 recognition was present in patients that did not have active malaria, which could be an effect of our vaccine design strategy as we use well-defined T and B cell epitopes to avoid the inclusion of regions of low immunogenic potential. We have previously demonstrated that our constructs are better recognized by naturally infected individuals when compared to native proteins and can circumvent the HLA restriction associated to these antigens 27 35 . These characteristics make our proteins not only desirable for vaccination but also useful for seroepidemiological studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations